ONLINE SHARING PLATFORMS AS A MEDIUM FOR THE EMERGENCE OF VIRAL CONTENT - Dermendjieva, Greta; Slavova, Rositsa (PEOPLE: International Journal of Social Sciences, 2018)
The research objectives of the paper are to look into the viral phenomenon emerging from online platforms for sharing video, pictures, tweets, GIFs, Facebook posts, and to discuss the emotional element as well as the key categories of the most popular content. The methodology includes reviewing, presenting and categorizing a selection of worldwide viral stories and some that have become popular in the UK and Bulgaria. The main focus is on features and content from YouTube, Facebook, Twitter and Instagram that has become viral during 2017. Our findings indicate that there are 9 main categories – Media, Entertainment, Celebrity, Domestic, Empathy, Jokes, Everyday life, Cause, and Politics – that could be distinguished in the explored selection. Another aspect we consider is the emotional effect the viral content has over the online users. We observe three dominant emotional states - positive, negative and ambivalent. The main outcome is that in almost 2/3 of the researched cases the emotion is positive. Future scope of research is to explore further what effect the viral content has over individuals, how fake content will affect the true viral content and the media agenda and whether media will focus on fake viral content and the consequences of it.